The three-dimensional heterostructure synthesis of ZnO/cellulosic fibers and its application for rubber composites. (16th June 2019) - Li, Yalan; Sun, Hao; Zhang, Yangyang; Xu, Min; Shi, Sheldon Q.
Abstract: Agglomeration of cellulosic fibers is the limiting factor in the fabrication of high-performance polymer composites. Here, we report a three-dimensional heterostructure of zinc oxide (ZnO)/cellulosic fiber hybrids to fabricate the multifunctional biomass rubber composites via the wet mixing method. The ultrasonic treatment and in-situ chemosynthesis method were used to incorporate ZnO particles on the surface of cellulosic fibers. The experimental results showed that ZnO particles with rod-like structures were grown on the surface of cellulosic fibers, and ultrasonic treated cellulosic fibers (UCF) could improve the aggregation and increase the growth content of ZnO particles from 16.5% to 23.2%. The composites microstructures showed that ZnO/UCF had a better dispersion and interface bonding than cellulosic fiber in natural rubber (NR) matrix. Moreover, ZnO/UCF/NR composites had higher tensile strength, stiffness, hydrophobic properties and antibacterial efficiency than pure NR. In view of the characterization of cellulosic fibers and inorganic particles, this three-dimensional structure hybrid would provide enormous opportunities to fabricate multifunctional biomass polymer composites.